Coordinated Management of COVID-19 Response: Lessons From Whole-of-Society and Whole-of-Health Strategies in Wuhan, China - Chen, Shanquan; Zhang, Pan; Zhang, Yun; Fung, Hong; Han, Yong; Law, Chi Kin; Li, Zhiqiang (Frontiers in Public Health, 2021)
Background: The outbreak of novel coronavirus disease 2019 (COVID-19) has been challenging globally following the scarcity of medical resources after a surge in demand. As the pandemic continues, the question remains on how to accomplish more with the existing resources and improve the efficiency of existing health care delivery systems worldwide. In this study, we reviewed the experience from Wuhan - the first city to experience a COVID-19 outbreak – that has presently shown evidence for efficient and effective local control of the epidemic. Material and Methods: We performed a retrospective qualitative study based on the document analysis of COVID-19-related materials and interviews with first-line people in Wuhan. Results: We extracted two themes (the evolution of Wuhan's prevention and control strategies on COVID-19 and corresponding effectiveness) and four sub-themes (routine prevention and control period, exploration period of targeted prevention and control strategies, mature period of prevention and control strategies, and recovery period). How Wuhan combatted COVID-19 through multi-tiered and multi-sectoral collaboration, overcoming its fragmented, hospital-centered, and treatment-dominated healthcare system, was illustrated and summarized. Conclusion: Four lessons for COVID-19 prevention and control were summarized: (a) Engage the communities and primary care not only in supporting but also in screening and controlling, and retain community and primary care as among the first line of COVID-19 defense; (b) Extend and stratify the existing health care delivery system; (c) Integrate person-centered integrated care into the whole coordination; and (d) Delink the revenue relationship between doctors and patients and safeguard the free-will of physicians when treating patients.